Management of Patient Food Delivery in Nutrition Installation, at the Melati Perbaungan Hospital in 2023 - Athira Demitri; Balqis Nurmauli Damanik (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Food management at the Melati Perbaungan hospital's nutritional installation has not gone well, menu planning has not run optimally. The vendor's delivery of food ingredients is not on time. The taste and texture of the food is still lacking. The material received is not suitable. Food storage areas do not meet standards. The aim of this research is to determine menu planning, procurement of food ingredients, receipt of food ingredients, storage of food ingredients and processing of food ingredients in the Nutrition Installation of Melati Perbaungan Hospital. This research was conducted using a descriptive research design with a qualitative approach. There were 5 research informants, namely the Main Informant consisting of the Head of the Nutrition Installation and the Person in Charge of the Cook, and the Supporting Informant consisting of the Waiter. The conclusion of the research is that the administration of food in the Nutrition Installation is still not in accordance with the steps or guidelines issued by the Indonesian Ministry of Health, there are still obstacles in the administration of patient food, for this reason it is recommended that the Nutrition Installation pay more attention and be more careful in paying attention to the food administration process in order to obtain good results and more guaranteed quality of patient food.